FACTORS INFLUENCING THE PERCEPTION OF TECHNOLOGY FIT IN MSMEs' TECHNOLOGY ADOPTION PROCESS - Soetopo, Elia Mahatma Rayhan; Syarafina, Viga; Alimin, Nadya Natasha; Sudibjo, Haryadi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to understand how micro, small, and medium enterprises perceive technology to decide whether or not to adopt it in their business. An in depth exploratory interview is conducted with each of the 12 participants. The results are then interpreted to understand them entirely while the findings are then categorized into a framework. This study finds that word of mouth, observations of peers, personal knowledge, and cross-generational interaction influence the perception on whether or not certain technology is fit for adoption. Meanwhile, safety, time, automation, opportunity, reliability, risk of malfunction, and ease of use are factors that are mostly perceived by users. This research is limited to understanding what the variables in the perception process are. Further research to test the validity in a large scale quantitatively is recommended for subsequent research. Keywords: Micro Small and Medium Enterprises (MSMEs); Digital Technology; Technology Adoption Process; Perception Factors; Technology Fit